Outbreaks of crown rot in Fragaria x ananassa caused by Neopestalotiopsis mesopotamica in Ecuador - Reyna, Hamilton Octavio Intriago-; Figueroa, Fernando José Rivas-; Casignia, Álvaro Mauricio Rivera-; Romero, Pablo Israel Álvarez-; Ferreira, Ana Francisca Tibúrcia Amorim Ferreira e (Emirates Journal of Food and Agriculture, 2021)
Strawberry crown rot is one of the most important diseases in Ecuador, with an incidence of up to 70% in the field. In the world, the strawberry crown rot is caused by different etiological agents, which makes efficient control of the disease difficult. In this study, 12 samples of strawberry plants were collected, at different stages of disease development, to determine the causative agent in Ecuador. The fungal isolates, consistent with the isolation, were identified and characterized using molecular and morphological approaches, and finally, Koch's postulate was carried out. Based on the form of growth, mycelial color, conidial morphology, and molecular characteristics (sequencing of the ITS and EF-1α region), the pathogen associated with the symptoms showed 99% similarity with the species Neopestalotiopsis mesopotamica. The result of Koch's postulates showed symptoms similar to those observed in field plants, in addition, the same inoculated isolate was recovered from artificially inoculated tissues. This is the first report of this fungus causing strawberry crown rot in Ecuador and in the world.